Plan de negocios para la creación de una empresa productora y comercializadora de jabón exfoliante a base de café en Santa Marta (2022)
The idea of developing this project is based on taking advantage of the coffee production resulting from the Sierra Nevada de Santa Marta, since it is such an important raw material in the coffee sector, which can be used to create new and innovative products that generate added value to the coffee bean and help mitigate the coffee economic situation. In this way, the main objective is the elaboration of a business plan that allows establishing the feasibility of creating a company dedicated to the production and commercialization of coffee-based soaps, taking into account that at present a large number of people have gained awareness of the importance of using natural products both as a way of respecting the environment and as a mechanism that promotes health. The methodology used is descriptive and mixed and contains an exposition of the theoretical foundations of feasibility studies for entrepreneurship. Having as main achievements to promote the economic and social development of the city, which for a long time has suffered from the lack of industrialization of existing natural resources, in addition to innovation in the use of natural resources through cosmetic products. For this reason, this business plan is based on a market study (segmentation, distribution, promotion, description, place and price) in order to identify the market segment and the necessary strategies to promote the product.